Anterior Segment Optical Coherence Tomography: Applications for Clinical Care and Scientific Research - Shan, Jing (Asia Pac J Ophthalmol (Phila), 2019)
Anterior segment optical coherence tomography (AS-OCT) imaging is a non-contact imaging technique that produces high-resolution images and quantitative measurements of the anterior segment and its anatomical structures. There has been rapid development of OCT technology over the past two decades, with the transition from time-domain to Fourier-domain OCT devices. By integrating these advancements in OCT technology, AS-OCT devices have evolved into versatile clinical and research tools for studies of the anterior segment and ocular surface. The primary purpose of this article is to review OCT technology and AS-OCT devices as well as applications of AS-OCT for clinical practice and scientific research. We first describe the different types of OCT technology, how they have been adapted for AS-OCT imaging, and differences between various AS-OCT devices. We then review the applications of AS-OCT for characterizing the anatomical structures of the anterior segment and aqueous outflow pathways, including the anterior chamber angle, trabecular meshwork, and Schlemm’s canal. We also describe glaucoma-related applications of AS-OCT imaging, which include evaluating patients for static and dynamic biometric risk factors of primary angle closure disease (PACD) and assessing the efficacy of glaucoma interventions, such as laser peripheral iridotomy (LPI) and glaucoma surgery. Finally, we review other clinical applications of AS-OCT imaging for detection and management of diseases of the ocular surface, cornea and lens.